Psychological security and deviant peer affiliation as mediators between teacher-student relationship and adolescent Internet addiction. (August 2017) - Jia, Jichao; Li, Dongping; Li, Xian; Zhou, Yueyue; Wang, Yanhui; Sun, Wenqiang
Abstract: A growing body of research has documented that teacher-student relationship is negatively associated with adolescent Internet addiction. However, little is known about the mediating mechanisms underlying this relation. The present study investigated whether psychological security and deviant peer affiliation mediate the link between teacher-student relationship and adolescent Internet addiction. A sample of 747 middle school students (51% male; M age = 13.73 years, SD = 1.00) completed questionnaires regarding demographics, teacher-student relationship, psychological security, deviant peer affiliation, and Internet addiction. After controlling for demographic covariates, the results revealed that: (a) teacher-student relationship was negatively associated with Internet addiction; (b) both psychological security and deviant peer affiliation partially mediated the link between teacher-student relationship and Internet addition in a parallel fashion; and (c) psychological security and deviant peer affiliation also sequentially mediated the link between teacher-student relationship and Internet addition. These findings have important implications for the prevention and intervention of adolescent Internet addiction. Highlights: Teacher-student relationship (TSR) was related to adolescent Internet addiction (IA). Psychological security (PS) mediated the link between TSR and IA. Deviant peer affiliation (DPA) mediated the link between TSR and IA. PS and DPA not only parallelly but also sequentially mediated the above relation.